Warm Autoimmune Hemolytic Anemia as First Presentation of Chronic Myeloid Leukemia: A Case Report - Ahmad Tawalbeh; Abdulrahman Al-Mashdali; Ahmad Al-Sabbagh; Anil Y. Ellahi; Mohamed A. Yassin (Case Reports in Oncology)
Introduction: Chronic myeloid leukemia (CML) is a myeloproliferative neoplasm characterized by the Philadelphia chromosome and uncontrolled granulocyte production. While autoimmune hemolytic anemia (AIHA) is commonly associated with lymphoproliferative disorders such as chronic lymphocytic leukemia, its occurrence in CML is rare, with only a few documented cases. Here, we report a case of concurrent chronic-phase CML and AIHA. Case Presentation: We present a 34-year-old female diagnosed with warm AIHA as the first presentation of CML. Diagnostic workup, including peripheral smear, revealed hemolysis with elevated lactate dehydrogenase and a positive direct antiglobulin test (DAT), along with a positive Philadelphia chromosome, confirming CML. Steroid therapy successfully managed the AIHA, leading to normalization of hemoglobin levels and subsequent tapering and discontinuation of steroids. Conclusion: While AIHA is a rare cause of anemia in CML, it should be considered during anemia evaluation, particularly in cases of CML relapse.